The Meaning of the Verses of Tasybih At-Tamtsil in Surah An-Nahl: An Analysis of Balaghah and Its Relevance to Islamic Religious Education - Nofrizal; Marlion, Ferki Ahmad (Journal of Contemporary Islamic Education, 2025)
This study aims to analyze the use of language styles tasybīh at-tamtsil in the Surah An-Nahl and reveal the relevance of the symbolic meaning of these verses to Islamic Religious Education (PAI). This research is a qualitative-descriptive study with a balaghah (bayān) and stylistic approach, through a literature study of the parable verses in the Surah An-Nahl, especially verses 74–75, 76, 91–92, and 112. The study results show that tasybīh at-tamtsil, the parables in this Surah, not only serve as rhetorical decoration, but also contain strong values of faith, morality, social, and spirituality. These parables illustrate the dangers of polytheism, the importance of keeping promises, social responsibility, and the threat to a society that denies blessings. This study concludes that integrating balaghah analysis into Islamic Religious Education (PAI) learning can strengthen students' understanding of the messages of the Qur'an aesthetically and educationally. Therefore, the balaghah approach can be a strategic alternative in developing an Islamic Religious Education (PAI) curriculum based on character and the values of monotheism.